Efek Larvasida Ekstrak Biji Buah Pepaya (Carica papaya L.) terhadap Larva Instar III Aedes aegypti L. - Arimaswati Arimaswati; La Ode Muhammad Sawaluddin; Hittah Wahi Sudrajat (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2017)
ABSTRACTThe larvacide Effects of Pawpaw’s Seed Extract (Carica papaya L) Againts Third Instar Larvae of Aedes aegypti L. (Biolarvacide Alternative Study). The aim of this research was to determine the Larvacide Effects of Pawpaw’s Seed Extract (C.papaya L) towards Third Instar Larvae of A. aegypti L. The research was conducted at the laboratory of Biology Education Department and laboratory of Chemistry Education Department, FKIP Halu Oleo University. Independent Variable (X) in the research is Pawpaw’s Seed Extract (C.papaya L) with concentration level are control or was not gived extract (X0), 0.125% (X1), 0.250% (X2), 0.375% (X3), 0.500% (X4), and 0.625% (X5) and Dependent variable (Y) is the mortality of Third Instar Larvae of Aedes aegypti L. The method in the research was used experimental method with Completely Randomized Design (CRD), 3 times repetitions, each group containing 20 larvae, so the total of sample were 360 larvae. The data analyze tecnic was used descriptive analyze to knowing the larvacide effect of Seed Extract (Carica papaya L) against the mortality of Third Instar Larvae of Aedes aegypti L., varians analyze and BJND test with a significant value 95% (α = 0.05) and probit analyze to calculate LC50value or lethal concentration 50%. The result of the descriptive analyzed shows in the control group there are not mortality of larvae. The highest concentration Pawpaw’s Seed Extract (Carica papaya L) was gived mortality of larvae is 0.625% (X5) or 100% (20 larvae) and low concentration is 0.125% (X1) or 45% (9 larvae). The result of sidik ragam analyze showing that the value of Fhitung> Ftabel,  there was a significant influence of the Pawpaw’s Seed Extract (Carica papaya L) for the mortality of Third Instar Larvae of Aedes aegypti L.The result of probit analyzed is LC50 value was gived 50% mortality of larvae is 0.154%.Keywords :Pawpaw’s Seed Extract (Carica papaya L), Larvacide, Third Instar Larvae of Aedes aegypti L.